2010
DOI: 10.5539/ijbm.v5n10p42
|View full text |Cite
|
Sign up to set email alerts
|

Tanzanian SMEs’ Perceptions towards Adoption of Supply Chain Management (SCM) Strategy

Abstract: Although a number of Small and Medium Enterprises (SME) in Tanzania economy is high, their share in national income is significantly low due to lack of efficiency. The choice to implement supply chain and supply chain management by SMEs will lower costs and increase efficiency, which will eventually help in lowering costs and increase gains to both SMEs and the country.In this research we have compared the differences in perceptions of small and medium-sized enterprises against large enterprises. The methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The same has been reported by Therakorn (2014) who found that the inability to manage SRM is a major obstacle impacting SMEs in Thailand. In Tanzania Katunzi and Zheng (2010) found that Tanzanian SMEs fail to effectively implement SRM due to the lack of trust among the partners. Nkwabi (2019) reported that poor coordination was a major factor impacting SRM in the Tanzanian SMEs.…”
Section: Srm In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same has been reported by Therakorn (2014) who found that the inability to manage SRM is a major obstacle impacting SMEs in Thailand. In Tanzania Katunzi and Zheng (2010) found that Tanzanian SMEs fail to effectively implement SRM due to the lack of trust among the partners. Nkwabi (2019) reported that poor coordination was a major factor impacting SRM in the Tanzanian SMEs.…”
Section: Srm In Smesmentioning
confidence: 99%
“…This results in the customers preferring imported goods or products from multinational companies (MNCs). In their study, Katunzi and Zheng (2010) reported that Tanzanian SMEs are reluctant to share information with their partners due to a lack of trust. Similarly, a review by Nkwabi (2019) revealed that SRM in the Tanzanian SMEs is weak due to the poor coordination between suppliers and their focal firms.…”
mentioning
confidence: 99%
“…Micro Small Medium Enterprises and Supply Chain Management a regional perspective Katunzi and Zheng (2010) performed a comparison of the SCM perceptions between Tanzanian SMEs and large firms. The research looked at four major issues: the benefits of SCM, the type of information sharing, the motivation for SCM integration and other collaborative SCM activities.…”
Section: Micro Small Medium Enterprises the African Perspectivementioning
confidence: 99%
“…The acquired business information can be used in addressing most of their growth barriers (Kazimoto, 2014). Conversely, Tanzanian SMEs are reluctant in sharing information to key players due to the fact that the information are likely to be acquired by their major rivals, and ultimately pose potential risks to their business interests and goals (Katunzi & Zheng, 2010). However, there are a lot of benefits gained when  Does risk planning influence the cost level, and output level of Tanzania-based bakeries under the moderation of the bakery age, and the gender of the bakery owner/manager respectively?…”
Section: Introductionmentioning
confidence: 99%